Prototype Design of Landfill Gas Pipe Leak Monitoring System Based on Microcontroller Node MCU ESP8266 with the Internet of Things Method - Aziz, Abdul; Zahra, Amalia (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The pipeline system is the main component of the gas distribution system in the waste power plant. In its development, the pipeline installation system requires continuous supervision and maintenance. It helped reduce losses due to incorrect installation conditions. Pipeline damage often occurs, such as the Landfill Gas (LFG) pipe leak and a decrease in the pipeline’s steam production level. The authors plan to make a tool to monitor a landfill gas (LFG) pipe leak in a waste power plant. This tool works because there is a gas leak in the pipeline. This tool will inform the officer who will repair the pipe leak. This tool installs at the top of each corner of the pipe, especially in the pipe connection section. The purpose is to examine the connecting part of the pipe since it is vulnerable to leakage. This tool installs on every pipe connection with one sensor. This tool equips a gas sensor that serves to detect gas leaks. The input is gas. If the gas sensor is on, it indicates a leak in the pipe, then the monitoring system is active and knows how much gas vapor exits from the pipe. If no gas enters, the sensor condition is inactive, and the condition will not leak.